PENGENALAN DAN PEMBELAJARAN URBAN FARMING MELALUI BUDIDAYA SISTEM HIDROPONIK DEEP FLOW TECHNIQUE (DFT) PADA SISWA SISWI SEKOLAH DASAR DAN MENENGAH DI KOTA MALANG - Putu Hadi Setyarini; Sisca Fajriani; Mochammad Roviq; Dwi Hadi Sulistyarini; Diana Aisyah (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2023)
A challenge in implementing green school initiatives is the lack of hydroponic cultivation learning facilities in the educational setting and the lack of space for planting productive plants in the environment of SDI As Salam and SMPIT As Salam as partners for community service activities. Teachers and students with little experience in hydroponic plant production techniques on small plots of land present another challenge for partners. All school constituents, namely teachers and students, are involved in hydroponic plant growth activities as part of the participatory rural appraisal (PRA) approach to activity implementation. Project for Strengthening Pancasila Student Profiles (P5) activities offer support through workshops for instructors and hydroponic farming techniques for teachers and students. The aims of mentoring are to: (1) teach fundamental information about hydroponic plant cultivation methods; (2) Integrate hydroponic culture learning facilities into the educational setting. The ability of students and teachers to carry out hydroponic activities, from planting seeds, caring for plants, and harvesting vegetable plants using the hydroponic method, is one indicator of the activity's success. Another is the presence of a hydroponic module in the partner environment that is used as a teaching tool for hydroponic cultivation in the school environment.